1998
DOI: 10.1002/(sici)1097-4636(199824)43:4<428::aid-jbm10>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

BoneSource? hydroxyapatite cement: A novel biomaterial for craniofacial skeletal tissue engineering and reconstruction

Abstract: BoneSource-hydroxyapatite cement is a new self-setting calcium phosphate cement biomaterial. Its unique and innovative physical chemistry coupled with enhanced biocompatibility make it useful for craniofacial skeletal reconstruction. The general properties and clinical use guidelines are reviewed. The biomaterial and surgical applications offer insight into improved outcomes and potential new uses for hydroxyapatite cement systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
359
1
9

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 404 publications
(381 citation statements)
references
References 8 publications
4
359
1
9
Order By: Relevance
“…36,37 CPC was approved in 1996 by the Food and Drug Administration for repairing craniofacial defects, thus becoming the first CPC for clinical use. 38 Traditional CPC was brittle and weak; however, the mechanical properties of CPC were improved by incorporating chitosan. 39,40 The CPC-chitosan scaffold supported the adhesion and proliferation of osteoblast cells and hMSCs.…”
mentioning
confidence: 96%
“…36,37 CPC was approved in 1996 by the Food and Drug Administration for repairing craniofacial defects, thus becoming the first CPC for clinical use. 38 Traditional CPC was brittle and weak; however, the mechanical properties of CPC were improved by incorporating chitosan. 39,40 The CPC-chitosan scaffold supported the adhesion and proliferation of osteoblast cells and hMSCs.…”
mentioning
confidence: 96%
“…Hydroxyapatite: By insertion porous HA wedges into the tibias of ten knees in seven patients having high tibial osteotomies, it was found that pores located at the interface, at the time of hardware removal, were completely filled with bone, and the bone depth formed increased consistently with time [137]. In another study, the transverse sections of porous HA implants placed in rabbit tibias demonstrated a new bone growth through the pores.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Neben diesen beiden Komplikationen führte seine fehlende ossäre Integrierbarkeit [12] dazu, dass Zemente auf Ca-P-Basis (Ca-P: Kalziumphosphat) mehr in den Focus rückten. Diese haben den Vorteil, dass sie resorbierbar sind und zu eigener Knochenstruktur umgebaut werden [6]. Außerdem erfolgt die Aushärtung nur knapp über Körpertemperatur [14].…”
Section: Vor-und Nachteile Der Zementartenunclassified